A SYNTACTIC ANALYSIS OF PREPOSITIONAL PHRASE WITHIN NOUN PHRASE USED IN THE STORY BY MARK TWAIN'S THE ADVENTURES OF HUCKLEBERRY FINN (USING X-BAR THEORY) - AMALIA., TUTI (2011)
This research deals with prepositional phrase within noun phrase in the story The Adventures of Huckleberry Finn by Mark Twain. The aims of this research are to identify the function and to describe the structural ambiguities of prepositional phrase within noun phrase in the story. The type of this research is descriptive qualitative. The data source of this research is the story by Mark Twain, The Adventures of Huckleberry Finn. The writer takes 279 data of prepositional phrase within noun phrase in sentences of The Adventures of Huckleberry Finn story. The method of collecting data is documentation and the steps are reading, selecting and collecting, and coding the data. The method of analyzing data is descriptive technique. The analysis of the data is by referring to the context of syntax by using x-bar theory then presenting phrase structure rules and phrase markers. This study shows the functions and structural ambiguities of prepositional phrase within noun phrase in sentences used in the story. The functions of prepositional phrase within noun phrase are: (1) A, (2) C, (3) A+A, (4) C+C, (5) A+C, (6) C+A, (7) A+C+A, (8) C+C+A, (9) C+A+A, (10) A+A+C, (11) A+A+A, (12) C+A+A+A, (13) A+C+A+C. The structural ambiguities of the prepositional phrase are found within noun phrase constructions are: (1) A+A, (2) C+C, (3) A+C, (4) C+A, (5) A+C+A, (6) C+C+A, (7) C+A+A, (8) A+A+C, (9) A+A+A, (10) C+A+A+A, (11) A+C+A+C.